ANTISPASMODIC EFFECTS OF YARROW (ACHILLEA MILLEFOLIUM L.) EXTRACT IN THE ISOLATED ILEUM OF RAT - Moradi, Mohammad-Taghi; Rafieian-Koupaei, Mahmoud; Imani-Rastabi, Reza; Nasiri, Jafar; Shahrani, Mehrdad; Rabiei, Zahra; Alibabaei, Zahra (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Achillea millefolium L. is cultivated in Iran and widely used in traditional medicine for gastrointestinal disorders. The aim of this study was to determine the effect of hydroalcoholic extract of A. millefolium on the contraction and relaxation of isolated ileum in rat. In this experimental study, aerial parts of A. millefolium were extracted by maceration in ethanol 70% for 72h. Terminal portion of ileum in 100 male Wistar rats was dissected and its contractions were recorded isotonically in an organ bath containing Tyrode solution (37 ºC, pH 7.4) under one gram tension. Acetylcholine (1mM) and KCl (60mM) were used to create isotonic contractions. Propranolol and Nω-Nitro-L-arginine methylester hydrochloride (L-NAME) were used to investigate the mechanisms of action prior to giving the extract to the relevant groups. Data were compared by ANOVA and Turkey's post hoc test.. The results showed that the ileum contraction was induced by KCl and acetylcholine induced contraction was significantly reduced by A. millefolium extract. The cumulative concentrations of A. millefolium relaxed the KCl and acetylcholine induced contractions (n=14, p<0.001). The inhibitory effect of extract on contraction induced by KCl and acetylcholine was not significantly affected neither by propranolol (1μM) nor by L-NAME (100 μM). There was no significant difference in the rate of relaxation by propranolol and L-NAME between the two groups. In conclusion, A. millefolium can inhibit contraction of smooth muscle of ileum in rat, and it can be used for eliminating intestinal spasms. These results suggest that the relaxatory effect of A. millefolium on ileum contractions can be due to the blockade of voltage dependent calcium channels. In addition, the β-adrenoceptors, cholinergic receptors and nitric oxide production are not powerful actors in inhibitory effect of A. millefolium. So, the nitric oxide and adrenergic systems may also be involved in the antispasmodic effect of A. millefolium.